2008
DOI: 10.1016/j.emc.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Intubation

Abstract: Airway management in the emergency department is a critical skill that must be mastered by emergency physicians. When rapid-sequence induction with oral-tracheal intubation performed by way of direct laryngoscopy is difficult or impossible due to a variety of circumstances, an alternative method or device must be used for a rescue airway. Retrograde intubation requires little equipment and has few contraindications. This technique is easy to learn and has a high level of skill retention. Familiarity with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…4 Although there are some known complications 5 like airway trauma, bleeding from nose/cricothyrotomy site, subcutaneous emphysema, infections and even variable success rates among practitioners 6 ; we did not encounter any problem. Recent advances of retrograde intubation and the combined use with fiber optic bronchoscope 7 , or ultrasound guidance 8 have renewed interest in this old technique.…”
Section: Discussionmentioning
confidence: 98%
“…4 Although there are some known complications 5 like airway trauma, bleeding from nose/cricothyrotomy site, subcutaneous emphysema, infections and even variable success rates among practitioners 6 ; we did not encounter any problem. Recent advances of retrograde intubation and the combined use with fiber optic bronchoscope 7 , or ultrasound guidance 8 have renewed interest in this old technique.…”
Section: Discussionmentioning
confidence: 98%
“…We therefore chose to use manikins that were specifically designed for percutaneous cricothyrotomy and RI. Other authors have also reported the successful use of manikins to simulate RI in humans [9, 35]. The manikin was designed for identification of the cricothyroid space; the cricotracheal area, however, was not easily palpable.…”
Section: Discussionmentioning
confidence: 99%
“…RI has been documented in pediatric patients as young as 5 months old [3]. The elective use of RI has been well documented in patients with angioedema [4], deep neck infections [5], burns [6], trismus [7], musculoskeletal disorders [8], and patients in the prehospital or emergency room [9] and trauma [10, 11] settings. Contraindications to the procedure include coagulation abnormalities, infection at the intended site of the puncture, pretracheal mass, and poorly palpable landmarks in the neck [12].…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world the new technology, or the expertise to use it, is not available. The retrograde technique, for good reasons, is still being recommended in the developed world, even in non‐anaesthetic environments [6].…”
mentioning
confidence: 99%